2014
DOI: 10.1002/2013jf002950
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the dynamics that scale cross‐shore headland relief on rocky coastlines: 1. Model development

Abstract: We have developed an exploratory model of plan view, millennial-scale headland and bay evolution on rocky coastlines. Cross-shore coastline relief, or amplitude, arises from alongshore differences in sea cliff lithology, where durable, erosion-resistant rocks protrude seaward as headlands and weaker rocks retreat landward as bays. The model is built around two concurrent negative feedbacks that control headland amplitude: (1) wave energy convergence and divergence at headlands and bays, respectively, that incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 107 publications
(161 reference statements)
2
49
0
Order By: Relevance
“…Klein and de Menezes, 2001;Sallenger et al, 2002;Bowman et al, 2009), which is also observed in numerical modelling studies of coastal change (e.g. Limber and Murray, 2011;Limber et al, 2014). Few studies, however, have examined the alongshore variability of wave energy transfer and erosion on low-sediment, rock coasts.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Klein and de Menezes, 2001;Sallenger et al, 2002;Bowman et al, 2009), which is also observed in numerical modelling studies of coastal change (e.g. Limber and Murray, 2011;Limber et al, 2014). Few studies, however, have examined the alongshore variability of wave energy transfer and erosion on low-sediment, rock coasts.…”
Section: Introductionmentioning
confidence: 86%
“…The focussing of wave energy and erosion around rock coastlines is controlled by prevailing wave and current directions (Carter et al, 1990), the availability and distribution of sediment (Sunamura, 1976(Sunamura, , 1982Limber and Murray, 2011), coastline planform and foreshore geometry (e.g. Klein and de Menezes, 2001;Bowman et al, 2009;Hapke et al, 2009;Limber and Murray, 2011;Limber et al, 2014), coastal bathymetry (e.g. Trenhaile, 1987;Komar, 1997), and relative rock strength and the resistance to wave energy transfer (Sunamura, 1977(Sunamura, , 1992.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional benefit is the direct coupling of models to data, especially valuable for exploratory models (Murray, 2003). Several studies have already used this approach, embedding machine learning components directly in models (e.g., Jain and Srinivasulu, 2004;Corzo et al, 2009;Limber et al, 2014) or during model calibration Hulscher, 2002, 2003;Ruessink, 2005). The focus of this article is on machine learning components that are directly embedded within physics-based models.…”
Section: Introductionmentioning
confidence: 99%